Study of the Efficiency of Electronic Postural Corrector in the Treatment and Prevention of Thoracic Hyperkyphosis in Children and Teenagers - Santos, Luiz Fernando Segato dos; Segato, Tiago Henrique Faccio; Ferro, Alessandra Monteiro; Cabreira, Leonardo Gabriel Quintino; Pinto, Alex Roschidt (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2014: Anais do IV Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2014)
In order to reduce postural problems in children and teenagers it was created an electronic postural corrector by the arguing technology that detects when the user is in an incorrect posture and warns him/her to behave properly. To ensure the efficiency of the device, this apparatus was tested on people with the problem of thoracic hyperkyphosis with the intuited to verify its efficiency regarding the treatment of this disease and on people who do not have the problem to verify its preventive efficiency. The test results prove the effectiveness of this equipment.